(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Many students have difficulty in understanding a research subject; some students do not know how to construct a research paper and do not have any confidence to defend their research paper. With this research group study, we will teach them how to do research. We will give motivation and advice to all students who get frustrated and pressured on making a research paper. This study will help the students with their difficulties in writing a research paper. A descriptive method was used in this study. This study aimed to identify and enhance the skills of students in their Research subject through the group study ofGrade 12 Accountancy, Business, and Management (ABM) Strandstudents at Bestlink College of the Philippines. Grade 12 ABM students should enhance their research skills. The researchers concluded that the reason why most students are not interested in making a research paper is because of the lack of knowledge. The results showed that this group study can help the students, especially grade 12 ABM students. Most students are not interested and have absenteeism because they do not know about making a research paper. Having good Internet access can allow the students to search about something related to their research.